PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGI VARIABEL MEDIASI PADA USAHA RUMAH MAKAN MAK ICUN TEMBILAHAN - Friananda Wahyu; Nursanti Aida; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The development of the culinary business is currently very fast, manybusiness people see a big opportunity in this business that can be used to make aprofit. The development of this culinary business, of course, is influenced by theneeds of the community, this is because culinary or food is a basic human need toget energy used in daily activities. This study aims to determine how big theinfluence of product quality, price on consumer loyalty with consumer satisfactionas a moderating variable. The type of data used is primary data collected with aquestionnaire as an instrument and structured interviews are used as acomplement in proving the results of the study. This study uses 120 consumers ofMak Icun Tembilahan Restaurant with the Non-Probability Sampling. The dataanalysis used is the classical assumption test, hypothesis testing, and pathanalysis as a data testing flow and is assisted by the SPSS application in terms ofdata processing. The results of this study indicate that product quality has asignificant positive effect on consumer satisfaction at the Mak Icun Restaurant inTembilahan. Price has a significant positive effect on consumer satisfaction at theMak Icun Restaurant in Tembilahan. Consumer Satisfaction has a significantpositive effect on Consumer Loyalty at the Mak Icun Restaurant in Tembilahan.Consumer Satisfaction has a significant effect as a mediation between ProductQuality and Consumer Loyalty with the calculation results being bigger than thedirect effect on the Mak Icun Restaurant in Tembilahan. Consumer Satisfactionhas a significant effect as a mediation between Price and Consumer Loyalty withthe calculation results being bigger than the direct effect on the Mak IcunRestaurant in Tembilahan. Keywords: Product Quality, Price, Consumer Loyalty, Consumer Satisfaction